Analisis Penjadwalan Perbaikan Gas Turbine Part dengan Metode PERT dan Gantt Chart pada Industri MRO - Rajagukguk, Leonard Yopandi; Winarsih, Neneng; Rahma, Rana Ardila; Arrafi, Muhammad Naufal (Industrika : Jurnal Ilmiah Teknik Industri, 2026)
Delays in the implementation of repair projects can significantly impact a company’s reputation and operational continuity. One of the main causes of such delays is the absence of effective project activity scheduling, which leads to untimely completion of tasks. Therefore, this study was conducted to minimize delays in the gas turbine repair process. By applying the Program Evaluation and Review Technique (PERT) and Gantt Chart methods to improve scheduling efficiency, this study aims not only to enhance the effectiveness of repair scheduling but also to forecast the achievable repair capacity within a one-year period, with a specific focus on the Transition Piece component. The findings indicate that the repair duration can be accelerated by 9%, and the repair capacity that can be achieved within one year is 22.22%. Keywords: Gantt Chart, PERT, Project Management, Scheduling